Selected Duets for clarinet: Volume II - VOXMAN, H. (Rubank, Inc., 1947)
Di dalam buku ini terdapat lagu: Duet-Based Upon the Sonata in C; Duet-Based Upon the Sonata in Eb; Duet-Based Upon the Sonata in Bb; Two Duets in Concert Style; Six Duets Based Upon the Works of Bach; Duet No.3-Based Upon the Duo in Bb for Clarinet and Basson by Beethoven